1996
DOI: 10.1007/bf00198925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ammonium sulfate on the phytotoxicity, foliar uptake, and translocation of imazamethabenz in wild oat

Abstract: Abstract. Experiments were conducted in greenhouse, growth chamber, and laboratory conditions to determine the effect of ammonium sulfate [(NH4)2504] on the phytotoxicity, foliar uptake, and translocation of imazamethabenz on wild oat. Rates of (NH4)2SO 4 up to 5% (w/v) applied with a greenhouse sprayer did not affect the phytotoxicity of the herbicide when the mix was applied at the one-to two-leaf stage. However, inclusion of 1 and 2% (NH4)2SO 4 increased the phytotoxicity of the herbicide when the mix was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…Previous studies have shown that the dose–response curves of a herbicide applied with and without surfactant is considered to be parallel (Kudsk et al . 1987; Hsiao et al . 1996; Devilliers et al.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the dose–response curves of a herbicide applied with and without surfactant is considered to be parallel (Kudsk et al . 1987; Hsiao et al . 1996; Devilliers et al.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies of dose–response trends following herbicide applications have used the log–logistic function to model dose–response relationships (e.g., Streibig, 1980, 1981; Lærke and Streibig, 1995; Seefeldt et al, 1995; Hsiao et al, 1996; Sandral et al, 1997). The log–logistic model expresses mean dose response as a sigmoidal, monotonic increasing or decreasing function in log(dose) that is symmetric about its point of inflection (Fig.…”
mentioning
confidence: 99%
“…A absorção foliar é comumente medida pela aplicação de gotículas de herbicidas radiomarcados nas folhas, medindo-se a radiação remanescente na superfície foliar em vários intervalos de tempo após a aplicação por meio da lavagem da folha (Al Khatib et al, 1992;Gaskin & Holloway, 1992;Green et al, 1992;Roggenbuck et al, 1994;Hsiao et al, 1996;Wahlers et al, 1997;Sprague et al, 1999). Um cuidado importante nessa técnica envolve a escolha do solvente para lavagem da superfície foliar.…”
Section: Introductionunclassified